Clinical Characteristics and Management of the Hydatid Cyst of the Liver: A Study from a Tertiary Care Center in Nepal - Utsav Joshi; Roshan Subedi; Amar Jayswal; Vishakha Agrawal (Journal of Parasitology Research)
A hydatid cyst of the liver is a significant yet neglected public health problem in Nepal. The present study was carried out to evaluate the demographic characteristics, clinical presentations, and management of the patients of the hydatid cyst of the liver in the setting of a developing country. It was a retrospective, descriptive analysis of 53 patients admitted in the department of surgery with the diagnosis of hydatid cyst of the liver based on clinical manifestations, imaging studies, or serology between 2016 and 2019. The median age of the patients was 36 years, with the age group of 25-45 years being the most commonly affected (23, 43.4%). 58.5% of the patients were female. Abdominal pain (49, 92.5%) and a palpable liver (17, 32.1%) were the most common complaint and physical finding in our study population, respectively. Abdominal ultrasonography and computed tomography scan were the major imaging studies used to establish a diagnosis. A unilocular and anechoic cystic lesion was the most frequent imaging finding. The right lobe of the liver harbored the cysts in the maximum number of patients. Surgery was the preferred modality of treatment (23, 43.4%), with pericystectomy being the most common form of surgical intervention. The hydatid cyst of the liver is a common cause of morbidity in Nepal. Clinical evaluation supplemented by imaging studies is required for diagnosis, and surgery remains the treatment of choice in most cases. To explain the epidemiological pattern of the disease, multicentric studies involving a larger sample of patients should be conducted.